“SAY WHAT CONSUME I’LL TELL YOU WHO YOU ARE”: FACTORS THAT INFLUENCE THE CONSUMPTION PATTERN AND THAT SHAPE THE PROFILE OF THE CURRENT CONSUMER - Borba, Sílvia Naiara de Souza (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The emphasis directed to food in the last decades has motivated measures and transformations in this field, including focusing on consumer positioning. The objective of this theoretical essay is to identify some factors that influence the changing patterns of consumption, mainly in the search for alternative foods. At first, most are addressed factors related to technological advances in production practices and their health implications. The second part goes on the merit of “embeddedness”, understanding the dynamics of recovery of products and connecting them to the place of origin and quality attributes. The final factor relates the change in consumption patterns to a society that values your satisfaction and consumerism is a way to renew their identity. After the rescue of these factors, it is concluded that there is a need to investigate consumers of differentiated products produced in rural areas, since from this point some policies of government support to small farmers can be reformulated or maybe implemented in accordance with the characteristic of certain locations and demands.